What drives productivity growth in the new EU member states? The case of Poland - Marcin Kolasa (European Central Bank (ECB), 2005)
This paper considers productivity developments in the new EU member states and provides evidence on factors driving productivity growth in these countries, focusing on a panel of Polish manufacturing industries. Companies in Poland seem to benefit significantly from transfer of technologies that have been accumulated in more developed economies. By contrast, no strong evidence is found on immediate technology transfer. Another result is a significant effect of domestic innovation activity. There are signs that market reforms also boosted efficiency, whereas the role of reallocation of production factors towards more productive activities was marginal. Bearing in mind all methodological and data-related caveats, as well as cross-country diversity, caution is required while interpreting the findings and extrapolating them to other new member states. However, the results obtained provide some policy implications and make the case for taking into account domestic innovation activity while constructing endogenous growth models for the EU catching-up economies.
Keywords: C23; O31; O47; 330; convergence; innovation; manufacturing; multi-factor productivity; new Member States; Produktivität; Schätzung; Polen